Greening of human resource development subsystems for environmental management and performance: the ADKAR model perspective - Osolase, Ehikioya Hilary; Mohd Rasdi, Roziah; Dato Mansor, Zuraina (Human Resource Management Academic Research Society, 2022)
The focus of this paper and significance of the topic is to evaluate green human resource development (Green HRD) practices, and also discuss the greening of human resource development (HRD) subsystems. The greening of HRD subsystems help employees and organizations to engage in environmental management and performance, which helps to mitigate against the impact from climate change, global warming, and environmental degradation. The methodology applied for the study was through the review of several literature on Green HRD, HRD, ADKAR model, green practices in academic institutions, hotel and manufacturing industries. Literature on selected countries with green policies was also retrieved. Published academic articles and other online sources accessed were from 2001 to 2022. The findings from the study revealed that through the features of ADKAR model (green awareness, green desire, green knowledge, green ability, and green reinforcement), the four subsystems of HRD (green training and development, green reward, green performance appraisal, and green feedback mechanism) which were investigated for this study, can be successfully greened. In greening the subsystems of HRD, employees and organizations are able to achieve a high scorecard of environmental management and performance in their various activities. Therefore, to conclude this study, further research is proposed. Through quantitative, qualitative, or mixed-method research methodology, and using the ADKAR model, future researches can empirically test the HRD subsystems inherent in organizations. Either in the public or private sector. Through review of literature, further researches can also focus on other HRD subsystems like career development, organizational development, counselling, role analysis, quality circle, and potential appraisal.